Preview control for a semi–active suspension system. (4th August 2014) - Soliman, A.M.A.; Crolla, D.A.
The use of preview, i.e. 'look–ahead', information about the road surface input, has been shown to offer substantial performance benefits for fully active and limited bandwidth active suspension systems. This paper investigates whether similar levels of performance improvements can be obtained for semi–active systems, bearing in mind this class of system is only capable of dissipating energy, in contrast to active systems which can also input energy. The study is theoretical and is based on a quarter–car model. The Pade approximation technique is used to represent the effect of preview time associated with the look–ahead sensor information about the ground input. The results reveal an important finding, i.e. that the semi–active system with preview provides the same level of performance as the fully active system without preview.